Tracking Private WhatsApp Discourse About COVID-19 in Singapore: Longitudinal Infodemiology Study - Edina YQ Tan; Russell RE Wee; Young Ern Saw; Kylie JQ Heng; Joseph WE Chin; Eddie MW Tong; Jean CJ Liu (JMIR Publications, 2021)
BackgroundWorldwide, social media traffic increased following the onset of the COVID-19 pandemic. Although the spread of COVID-19 content has been described for several social media platforms (eg, Twitter and Facebook), little is known about how such content is spread via private messaging platforms, such as WhatsApp (WhatsApp LLC). ObjectiveIn this study, we documented (1) how WhatsApp is used to transmit COVID-19 content, (2) the characteristics of WhatsApp users based on their usage patterns, and (3) how usage patterns link to COVID-19 concerns. MethodsWe used the experience sampling method to track day-to-day WhatsApp usage during the COVID-19 pandemic. For 1 week, participants reported each day the extent to which they had received, forwarded, or discussed COVID-19 content. The final data set comprised 924 data points, which were collected from 151 participants. ResultsDuring the weeklong monitoring process, most participants (143/151, 94.7%) reported at least 1 COVID-19-related use of WhatsApp. When a taxonomy was generated based on usage patterns, around 1 in 10 participants (21/151, 13.9%) were found to have received and shared a high volume of forwarded COVID-19 content, akin to super-spreaders identified on other social media platforms. Finally, those who engaged with more COVID-19 content in their personal chats were more likely to report having COVID-19-related thoughts throughout the day. ConclusionsOur findings provide a rare window into discourse on private messaging platforms. Such data can be used to inform risk communication strategies during the pandemic. Trial RegistrationClinicalTrials.gov NCT04367363; https://clinicaltrials.gov/ct2/show/NCT04367363